Determinantes das estruturas de governança das fecularias na compra de mandioca no estado do Paraná - Felipe, Fábio Isaias (2015)
In the agri-chain of cassava starch in Brazil, the supply of firms is through different governance structures. These structures range from the purchase via the spot market - without any contractual control over the production - to the hierarchy or vertical integration, structure in which the company is growing in own areas, with full control over the production. Between these two extremes were also identified other governance structures, which are called Hybrid arrangements that can approach the spot market or hierarchy. This essay aimed to identify the factors that influence the decisions of the paranaenses starch factories on the governance structures in buying - cassava supply in the state of Paraná. The specific objectives are: a) show if there is specifics that support the necessity to search for a particular organizational arrangement to the detriment of business through the spot market in the state of Paraná; b) analyze the factors that justify the choices of cassava starch factories for plural or singular forms in the state of Paraná; c) comparing the efficiency of the use or the combination of governance mechanisms in cassava starch factories in Paraná State, considering idleness as an index for the year 2014. The entire analysis of this essay is based on the theoretical assumptions of the New Institutional Economics (NIE), especially in the Transaction Cost Economics (TCE). In this essay the explanatory method was the most appropriate, once for this it sought to identify the determining factors for the occurrence of the phenomena observed: i) coexistence of plural forms of governance to coordinate the purchase of cassava by starch factories in Brazil and in the state of Paraná. This research method more approach the scientific knowledge to the real world as it explains the reason and why the facts. In the case of cassava, the characteristics of transactions - temporal and locational characteristics, as well as uncertainty and frequency – were not relevant for the choice of governance structures, on the contrary to what literature indicates. Even considering these characteristics, in Brazil and in the state of Paraná was prevailing the coordination by the spot market. The results also indicated the existence of a plurality of transactions in many levels - with different agents, and similar agents in a single transaction - since the combination of different governance structures can reduce transaction costs and even increase the efficiency of industry here measured by the reduction of industrial idleness.